Black Sea Biological Diversity Romania. - Petranu, Adriana; Moldoveanu, Mariana (PANGAEA, 2015)
The Poluare 1982-1983 dataset contains zooplankton data collected allong 7 transect in front of the Romanian littoral. Zooplankton sampling was undertaken at 14 stations where samples were collected using a Juday closing net in the 0-2m layer . The dataset includes samples analysed for mesozooplankton species composition and abundance. Sampling volume was estimated by multiplying the mouth area with the wire length. Total biomass was estimated using a tabel with wet weight for each species an stage. Taxon-specific mesozooplankton abundance was counted under the microscope.
Abundance and biomass of mesozooplankton in the western Black sea during Steaua de Mare cruise in 1982 and 1983
Keywords: Acartia clausi, c1; Acartia clausi, c2; Acartia clausi, c3; Acartia clausi, c4; Acartia clausi, c5; Acartia clausi, female; Acartia clausi, male; Acartia clausi, nauplii; Anomalocera patersoni, female; Bivalvia, larvae; Black Sea; Bosmina longirostris; Brachionus sp.; Calanipeda aquaedulcis, c2; Calanipeda aquaedulcis, c3; Calanipeda aquaedulcis, c4; Calanipeda aquaedulcis, female; Calanipeda aquaedulcis, juvenile; Calanipeda aquaedulcis, male; Calanus euxinus, c4; Calanus euxinus, c5; Calanus euxinus, nauplii; Centropages ponticus, c3; Centropages ponticus, c5; Centropages ponticus, female; Centropages ponticus, male; Centropages ponticus, nauplii; Cirripedia, cypris; Cirripedia, nauplii; Computed/Converted; Counting; Coxliella helix; Ctenophora, biomass; Cyclops sp., juvenile; Cyclops vicinus, female; Cyclops vicinus, juvenile; Cyclops vicinus, male; Daphnia longispina; Date/Time of event; Decapoda, larvae; DEPTH, water; Estimated; Gastropoda, larvae; Harpacticoida; Helicostomella subulata; JUDAY; Juday net; Mesozooplankton; Mesozooplankton, biomass, wet mass; Metacylis mediterranea; Noctiluca, biomass; Noctiluca scintillans; Oikopleura dioica; Oithona nana, female; Oithona nana, juvenile; Oithona nana, male; Oithona nana, nauplii; Oithona similis, female; Oithona similis, juvenile; Paracalanus parvus, c2; Paracalanus parvus, c3; Paracalanus parvus, c4; Paracalanus parvus, c5; Paracalanus parvus, female; Paracalanus parvus, male; Paracalanus parvus, nauplii; Penilia avirostris; Pleopis polyphemoides; Pleurobrachia pileus; Pol_Apr_82_CN1; Pol_Apr_82_CN2; Pol_Apr_82_CO1; Pol_Apr_82_CO2; Pol_Apr_82_CS1; Pol_Apr_82_CS2; Pol_Apr_82_ES1; Pol_Apr_82_ES2; Pol_Apr_82_MG1; Pol_Apr_82_MG2; Pol_Apr_82_NO1; Pol_Apr_82_NO2; Pol_Apr_82_VV1; Pol_Apr_82_VV2; Pol_Apr_83_CN2; Pol_Apr_83_CO1; Pol_Apr_83_CO2; Pol_Apr_83_CS1; Pol_Apr_83_CS2; Pol_Apr_83_ES1; Pol_Apr_83_ES2; Pol_Apr_83_MG1; Pol_Apr_83_MG2; Pol_Apr_83_NO1; Pol_Apr_83_NO2; Pol_Apr_83_VV1; Pol_Apr_83_VV2; Pol_Aug_82_CN1; Pol_Aug_82_CN2; Pol_Aug_82_CO1; Pol_Aug_82_CO2